Analisis Faktor yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan Perusahaan Property dan Real Estate di BEI Tahun 2011-2014. - Hidayatullah, Muhammad; Diansari, Rani Eka (Universitas PGRI Yogyakarta, 2016)
This study aims to examine factors that influence the timeless of financial report. The independent variable of this research are profitability, firmsize, and the public ownership, while the dependent variable is timeless. The population of this research are property and real estate companies which are listed in Indonesian Stock Exchange 2011-2014. The sample in this research is taken by using purposive sampling method with some carracteristics and consist of 30 companies. This research used secondary data from www.idx.co.id and the method of analysis used logistic regression analysis. The results show that the profitability is significantly influenced to the timeless of financial report, while both the firmsize and public ownership are not significantly influenced the timeless of financial report.